2017
DOI: 10.1096/fj.201601138rr
|View full text |Cite
|
Sign up to set email alerts
|

Desmoglein 2 modulates extracellular vesicle release from squamous cell carcinoma keratinocytes

Abstract: Extracellular vesicles (EVs) are nanoscale membrane-derived vesicles that serve as intercellular messengers carrying lipids, proteins, and genetic material. Substantial evidence has shown that cancer-derived EVs, secreted by tumor cells into the blood and other bodily fluids, play a critical role in modulating the tumor microenvironment and affecting the pathogenesis of cancer. Here we demonstrate for the first time that squamous cell carcinoma (SCC) EVs were enriched with the C-terminal fragment of desmoglein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 55 publications
(78 reference statements)
2
72
0
Order By: Relevance
“…We showed highly surviving cancer stem‐like cells to robustly secrete EpCAM‐contained EVs . It was also shown that levels of epidermal growth factor (EGFR) were elevated in serum EVs as well as primary tumors in patients suffering from head and neck squamous cell carcinoma . Notably, HSP90 was also found in EVs secreted by cancer cells …”
Section: Introductionmentioning
confidence: 88%
“…We showed highly surviving cancer stem‐like cells to robustly secrete EpCAM‐contained EVs . It was also shown that levels of epidermal growth factor (EGFR) were elevated in serum EVs as well as primary tumors in patients suffering from head and neck squamous cell carcinoma . Notably, HSP90 was also found in EVs secreted by cancer cells …”
Section: Introductionmentioning
confidence: 88%
“…The stop codon of the human Dsg2 cDNA was removed and sub-cloned into vector pEGFP-N1 (Clontech, Mountain View, CA) upstream of the GFP as previously described in detail [13,20,21]. For Dsg2cacs cDNA, two cysteine point mutations were generated using the QuikChange site directed mutagenesis kit (Stratagene, San Diego, CA) [20].…”
Section: Generation Of Dsg2 Mutant Cell Linesmentioning
confidence: 99%
“…The non-cell autonomous effect of Dsg2 could be explained by increased urokinase-type plasminogen activator and/or IL-6 production or by transfer of the upregulated receptors by extracellular vesicles or exosomes by Dsg2-expressing cells (Figure 4). In this regard, we have previously described that Dsg2 can alter the number and protein content of extracellular vesicles released by keratinocytes (Overmiller et al, 2017).…”
Section: Discussionmentioning
confidence: 96%